Analisis Kinerja Pelayanan Rumah Sakit Berdasarkan Indikator BOR, ALOS, TOI, dan BTO Studi Kasus pada Rumah Sakit Umum Daerah di Indonesia - Ardiani, Sus Retha Mona; Paramarta, Vip; Kosasih, Kosasih (Lembaga Teewan Journal Solutions, 2026)
Inpatient services are one of the main indicators of hospital performance. This study aims to analyze the inpatient service performance of RSUD Raja Ahmad Tabib Batam based on the indicators of Bed Occupancy Rate (BOR), Average Length of Stay (ALOS), Turnover Interval (TOI), and Bed Turnover Rate (BTO) for the period 2023–2025. This research uses a quantitative descriptive design with a retrospective approach. Data were obtained from the Daily Inpatient Census (SHRI) over three years. The results showed an average BOR of 78.4% (standard 60-85%), ALOS of 4.2 days (standard 6-9 days), TOI of 1.1 days (standard 1-3 days), and BTO of 68.5 times per year (standard 40-50 times). Overall, the inpatient performance of RSUD Raja Ahmad Tabib Batam is in the efficient category. However, the low ALOS needs special attention so as not to affect the quality of service. This study is expected to serve as an evaluation material and improvement of hospital bed management.